Non-suicidal self-injury motivations in the light of self-harm severity indicators and psychopathology in a clinical adolescent sample - Reinhardt, Melinda; Rice, Kenneth G.; Horváth, Zsolt (Frontiers in Psychiatry, 2022)
Adolescents with psychiatric problems are also considered a vulnerable population in terms of nonsuicidal self-injury (NSSI). In the current study, we examined the associations of interpersonal and intrapersonal NSSI motivations with several NSSI severity indicators and psychopathological characteristics. In a cross-sectional research design, 158 adolescents (83.5% girls; mean age=16.10 ys; SD=1.49) who have received inpatient or outpatient psychiatric treatment completed the Inventory of Statements About Self-Injury, the Strengths and Difficulties Questionnaire, and the Self-Critical Rumination Scale. More than two-thirds of the sample (75.3%; n=119) reported at least one episode of NSSI in their life, and 45.38% (n=54) have engaged in NSSI in the past month (current self-injury). The results indicated that only intrapersonal NSSI functions were linked to NSSI severity indicators (current and repetitive NSSI, versatility), interpersonal functions were not. Furthermore, a number of psychopathological features (co-occurring mental disorders, presence of a mood disorder, more internalizing mental illness symptoms, and more pronounced self-critical rumination) were associated with engaging in NSSI for intrapersonal reasons. We also identified other differences within the specific intrapersonal NSSI motivations. It should be highlighted that the anti-suicide function of NSSI behaved in exactly the opposite way as the other intrapersonal motivations. All this points to the fact that in clinical settings, detailed assessment of NSSI motivations and severity indicators can help to develop a more effective treatment plan.